BIOGEOGRAPHY OF PLANKTONIC FORAMINIFERS IN THE PALEOCENE AND EOCENE NORTH PACIFIC - Basov I.A. (My University, 1999)
Changes in species diversity, taxonomy, and structure of late Paleocene-Eocene planktonic foraminiferal assemblages are discussed using the results of the analysis of their distribution in the North Pacific region along the profile from the Mid-Pacific Mountains in the south to northern Kamchatka in the north. It is shown that, during the late Paleocene and early Eocene, the North Pacific was populated by a foraminiferal assemblage dominated by representatives of the equatorial-tropical (Morozovella) and tropical-subtropical (Acarinina) genera. Their role slightly decreases only in northern Kamchatka. In the middle Eocene, planktonic foraminifers of the North Pacific showed a distinct latitudinal differentiation, and this situation was particularly well-expressed in the late Eocene. Similar tendency is also characteristic of the southern high-latitude zone of the Pacific. As a whole, changes in the taxonomic composition of planktonic foraminiferal assemblages, their structure, and distribution in the study region during the late Paleocene and Eocene are similar to those established previously in the Atlantic.
Keywords: Eocene; Paleocene; Кайнозой::Палеоген::Эоцен; Cenozoic::Paleogene::Paleocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Палеоцен